Diagnostic and Surgical Decision-Making for Degenerative Cervical Myelopathy: A Survey With Post-Stratification Analysis - Chauhan, Rohil; Segar, Anand; Diwan, Ashish; Najib, Nashwa; Zeng, Irene; Rice, David; White, Steve (SAGE Publishing, 2025)
Study Design Online questionnaire following the CHERRIES framework. Objectives Degenerative cervical myelopathy (DCM) is a heterogenous condition with a broad clinical presentation profile. Understanding the adoption of clinical signs and symptoms for both diagnostic and surgical decision-making could inform the development of standardised diagnostic criteria for DCM. Therefore, we sought to survey orthopaedic spine surgeons and neurosurgeons in secondary care across Australasia (New Zealand and Australia). Methods An online 19-item questionnaire was distributed to orthopaedic spine surgeons and neurosurgeons across Australasia. It examined factors influencing diagnostic and surgical decision-making, including responses to clinical vignettes. Post-stratification weighting was applied and an exploratory post-hoc pattern analysis was performed. Results Seventy-two completed responses were analysed. For diagnosis, gait clumsiness (86.1%), hand clumsiness (76.4%) and reduced hand dexterity (75.0%) were the most frequently selected symptoms, and hyperreflexia (83.3%) and ankle clonus sign (68.1%) were the most commonly selected clinical signs. Symptom severity, myelomalacia, and extent of cord compression were ranked as the top 3 variables influencing surgical decision-making for over 70% of surgeons. In clinical vignettes, most (72.2%) chose serial observation for asymptomatic cord compression; however, accompanying myelomalacia was found to increase the chance of offering surgery from 5.6% to 34.7%. Conclusions Although several signs and symptoms were commonly used to diagnose DCM, a broad range of features were employed, reflecting substantial variability amongst Australasian surgeons. Surgical decision-making also varied, particularly for asymptomatic cord compression with myelomalacia. These findings reinforce the need for standardized diagnostic criteria and referral pathways.
Keywords: Asia Pacific; Australia; New Zealand; degenerative cervical myelopathy; diagnosis; neurosurgery; orthopaedics; surgical decision-making; 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Clinical Research; Neurosciences; 7.3 Management and decision making; 3202 Clinical sciences